2004
DOI: 10.1038/sj.jea.7500294
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study using scripted ventilation conditions to identify key factors affecting indoor pollutant concentration and air exchange rate in a residence

Abstract: A pilot study was conducted using an occupied, single-family test house in Columbus, OH, to determine whether a script-based protocol could be used to obtain data useful in identifying the key factors affecting air-exchange rate (AER) and the relationship between indoor and outdoor concentrations of selected traffic-related air pollutants. The test script called for hourly changes to elements of the test house considered likely to influence air flow and AER, including the position (open or closed) of each wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 13 publications
(11 reference statements)
1
28
0
Order By: Relevance
“…Tables Table 1 Publications (Turpin et al 2007) 48 hrs Los Angeles; Houston; Elizabeth, NJ,US X P X X 157-275 17 (Croxford et al 2006) 1 week London, UK C 270 18 (Jia et al 2008) 3-4 days Michigan, US X X X 251-257 19 (Jo and Lee 2006) 2 hrs Daegu, South Korea C 240 20 (Heroux et al 2009) 24 hrs Saskatchewan, Canada X X NA 217 21 (Long et al 2000) 12 hrs Boston, Massachusetts, US X P 211 22 (Offermann 2009) 24 hrs California, US X X P,C, N X X X 31-211 23 (Jarvis et al 2005) 14 days United Kingdom N 203 24 (Edwards et al 2001) 48 hrs Helsinki, Finland X X X 201 25 (Gordon et al 1999) 6-7 days Arizona, US X X 185 26 (Jia et al 2008) 3-4 days Southeast Michigan, US X X X NA 159 27 (Sexton et al 2004) 2 days Minneapolis/St. Paul, Minnesota, US X X 132 28 (Rudel et al 2003) 24 hrs Cape Cod, Massachusetts, US X X 30-120 29 (Fromme et al 2004) 7-8 hrs Berlin, Germany X 115 30 (Simons et al 2007) 3 days Baltimore, Maryland, US X O, P, N 95-109 31 (Weisel 2006) 24 hrs New Jersey, US X X 7-100 32 (Zota et al 2005) 2 weeks Boston, Massachusetts, US X N 100 33 (Guo et al 2009) 24 hrs Hong Kong X X 100 34 (Gilbert et al 2006) 7 days Quebec City, Canada N X 96 36 (Miller et al 2009) 24 hrs Commerce City, Colorado, US X C,P 92-97 37 (Phillips et al 2005) 24 hrs Oklahoma, US X X 90 38 (Kinney et al 2002) 48 hrs West central Harlem, New York, US X P X X X 18-88 39 (Lee et al 2002) 6 days Southern California, US X N,O 92-106 40 (Sorensen et al 2005) 48 hrs Copenhagen, Denmark P,N 73-87 41 (Dodson et al 2008) 24 hrs Boston, Massachusetts, US X X X 83 42 (Janssen et al 2005) 24 hrs Amsterdam/Helsinki P X 82 43 (Garrett et al 1999) 24 hrs Latrobe Valley, Victoria, Australia N 80 44 24 hrs Ottawa, Ontario, Canada X X 75 45 (Raymer et al 2009) 24 hrs Wisconsin, California, US X X X 47-70 46 (Johnson et al 2004) 3 days Columbus, Ohio, US X C 32-67 47 …”
Section: Discussionmentioning
confidence: 99%
“…Tables Table 1 Publications (Turpin et al 2007) 48 hrs Los Angeles; Houston; Elizabeth, NJ,US X P X X 157-275 17 (Croxford et al 2006) 1 week London, UK C 270 18 (Jia et al 2008) 3-4 days Michigan, US X X X 251-257 19 (Jo and Lee 2006) 2 hrs Daegu, South Korea C 240 20 (Heroux et al 2009) 24 hrs Saskatchewan, Canada X X NA 217 21 (Long et al 2000) 12 hrs Boston, Massachusetts, US X P 211 22 (Offermann 2009) 24 hrs California, US X X P,C, N X X X 31-211 23 (Jarvis et al 2005) 14 days United Kingdom N 203 24 (Edwards et al 2001) 48 hrs Helsinki, Finland X X X 201 25 (Gordon et al 1999) 6-7 days Arizona, US X X 185 26 (Jia et al 2008) 3-4 days Southeast Michigan, US X X X NA 159 27 (Sexton et al 2004) 2 days Minneapolis/St. Paul, Minnesota, US X X 132 28 (Rudel et al 2003) 24 hrs Cape Cod, Massachusetts, US X X 30-120 29 (Fromme et al 2004) 7-8 hrs Berlin, Germany X 115 30 (Simons et al 2007) 3 days Baltimore, Maryland, US X O, P, N 95-109 31 (Weisel 2006) 24 hrs New Jersey, US X X 7-100 32 (Zota et al 2005) 2 weeks Boston, Massachusetts, US X N 100 33 (Guo et al 2009) 24 hrs Hong Kong X X 100 34 (Gilbert et al 2006) 7 days Quebec City, Canada N X 96 36 (Miller et al 2009) 24 hrs Commerce City, Colorado, US X C,P 92-97 37 (Phillips et al 2005) 24 hrs Oklahoma, US X X 90 38 (Kinney et al 2002) 48 hrs West central Harlem, New York, US X P X X X 18-88 39 (Lee et al 2002) 6 days Southern California, US X N,O 92-106 40 (Sorensen et al 2005) 48 hrs Copenhagen, Denmark P,N 73-87 41 (Dodson et al 2008) 24 hrs Boston, Massachusetts, US X X X 83 42 (Janssen et al 2005) 24 hrs Amsterdam/Helsinki P X 82 43 (Garrett et al 1999) 24 hrs Latrobe Valley, Victoria, Australia N 80 44 24 hrs Ottawa, Ontario, Canada X X 75 45 (Raymer et al 2009) 24 hrs Wisconsin, California, US X X X 47-70 46 (Johnson et al 2004) 3 days Columbus, Ohio, US X C 32-67 47 …”
Section: Discussionmentioning
confidence: 99%
“…There are some ways to reduce the concentration of formaldehyde indoors, such as choosing environmentally-friendly decorating materials, ensuring thorough ventilation, delaying residency, and installing cleansing equipment [16][17][18] . Our study confirmed that the use of environmentally-friendly decorating materials, longer storage of materials after decoration, and increased ventilation helped to reduce formaldehyde pollution.…”
Section: Protective Methodsmentioning
confidence: 99%
“…Some studies reported AERs using perfluorocarbon tracer (PFT) compounds (Dietz et al, 1981(Dietz et al, , 1986Leaderer et al, 1985;Cheong and Riffat, 1995). The most commonly used method is the sulfur hexafluoride (SF 6 ) decay test, which has been reported in many studies (McBride et al, 1997;Johnson et al, 2004) when commercial availability of instruments for SF 6 tests has made AER measurements possible. However, the instrumentation for these methods is usually bulky and expensive.…”
Section: Introductionmentioning
confidence: 99%